The role of the locus coeruleus in the generation of pathological anxiety. (July 2020) - Morris, Laurel S.; McCall, Jordan G.; Charney, Dennis S.; Murrough, James W.
This review aims to synthesise a large pre-clinical and clinical literature related to a hypothesised role of the locus coeruleus norepinephrine system in responses to acute and chronic threat, as well as the emergence of pathological anxiety. The locus coeruleus has widespread norepinephrine projections throughout the central nervous system, which act to globally modulate arousal states and adaptive behavior, crucially positioned to play a significant role in modulating both ascending visceral and descending cortical neurocognitive information. In response to threat or a stressor, the locus coeruleus–norepinephrine system globally modulates arousal, alerting and orienting functions and can have a powerful effect on the regulation of multiple memory systems. Chronic stress leads to amplification of locus coeruleus reactivity to subsequent stressors, which is coupled with the emergence of pathological anxiety-like behaviors in rodents. While direct in vivo evidence for locus coeruleus dysfunction in humans with pathological anxiety remains limited, recent advances in high-resolution 7-T magnetic resonance imaging and computational modeling approaches are starting to provide new insights into locus coeruleus characteristics.